Respuesta :

Answer:

hope it will help u......................

Ver imagen Deepanshi

The function R(x) - S(x) is [tex]3x^{3} -2x^{2} +x-1[/tex].

What is function?

An expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable) is called function.

According to the given question.

We have two functions

[tex]R(x) = 3x^{3} +2x^{2} +x[/tex]

And, [tex]S(x) = 4x^{2} + 1[/tex]

Therefore, the function   R(x) - S(x) is given by

[tex]R(x) - S(x) = 3x^{3} +2x^{2} +x-(4x^{2} +1)[/tex]

[tex]\implies R(x) - S(x) = 3x^{3} +2x^{2} +x - 4x^{2} -1[/tex]

[tex]\implies R(x) - S(x) = 3x^{3} -2x^{2} +x-1[/tex]

Hence, function R(x) - S(x) is [tex]3x^{3} -2x^{2} +x-1[/tex].

Find out more information about function here:

https://brainly.com/question/12431044

#SPJ3